2017
DOI: 10.1016/j.jsams.2017.09.232
|View full text |Cite
|
Sign up to set email alerts
|

Assuming rater reliability of a movement competency screen – Is it true?

Abstract: relationship to the development of shoulder pain in this group of swimmers, perhaps further investigation of strength ratios in future large prospective investigations into risk factors in the development of shoulder pain is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During a systematic revision [2] it was shown that the general punctuation of poor quality of movement is associated with a higher risk of injury in the lower extremities. Mann et al [65] demonstrate that a total punctuation may be used in a more reliable way than an individual one when assessing movement. Despite the fact that the global punctuation system has been used in research, there is scientific evidence that contradicts this marking system [33].…”
Section: Discussionmentioning
confidence: 99%
“…During a systematic revision [2] it was shown that the general punctuation of poor quality of movement is associated with a higher risk of injury in the lower extremities. Mann et al [65] demonstrate that a total punctuation may be used in a more reliable way than an individual one when assessing movement. Despite the fact that the global punctuation system has been used in research, there is scientific evidence that contradicts this marking system [33].…”
Section: Discussionmentioning
confidence: 99%